2021
DOI: 10.3389/fnins.2021.685050
|View full text |Cite
|
Sign up to set email alerts
|

Direct Targeting of the Anterior Nucleus of the Thalamus via 3 T Quantitative Susceptibility Mapping

Abstract: Objective: Deep brain stimulation (DBS) of the anterior nucleus of the thalamus (ANT) is a potentially effective, minimally invasive, and reversible method for treating epilepsy. The goal of this study was to explore whether 3 T quantitative susceptibility mapping (QSM) could delineate the ANT from surrounding structures, which is important for the direct targeting of DBS surgery.Methods: We obtained 3 T QSM, T1-weighted (T1w), and T2-weighted (T2w) images from 11 patients with Parkinson’s disease or dystonia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Due to the high sensitivity to iron and myelin content in the brain tissue, QSM can provide superior imaging contrast between paramagnetic iron‐rich deep brain GM and the surrounding diamagnetic WM structures (Dimov et al, 2018 ; Kerl et al, 2012 ; Sun et al, 2015 ). It has been shown to facilitate the depiction of iron‐rich DBS targeting nuclei and sub‐nuclei from the surrounding WM structures, for example, the subthalamic nucleus (Alkemade et al, 2017 ; Liu et al, 2013 ), globus pallidus internus (Wei, Zhang, et al, 2019 ), sub‐nuclei of the thalamus (Li et al, 2019 ; Yu, Li, et al, 2021 ; Yu, Ren, et al, 2021 ; Zhang et al, 2018 ), and the dentate nucleus of the cerebellum (He et al, 2017 ). A previous study using 7.0‐T MRI susceptibility‐weighted imaging of the non‐human primate brainstem indicated that PPN shows higher susceptibility than its adjacent WM structures, such as the SCP and the lemniscal system (Zitella et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high sensitivity to iron and myelin content in the brain tissue, QSM can provide superior imaging contrast between paramagnetic iron‐rich deep brain GM and the surrounding diamagnetic WM structures (Dimov et al, 2018 ; Kerl et al, 2012 ; Sun et al, 2015 ). It has been shown to facilitate the depiction of iron‐rich DBS targeting nuclei and sub‐nuclei from the surrounding WM structures, for example, the subthalamic nucleus (Alkemade et al, 2017 ; Liu et al, 2013 ), globus pallidus internus (Wei, Zhang, et al, 2019 ), sub‐nuclei of the thalamus (Li et al, 2019 ; Yu, Li, et al, 2021 ; Yu, Ren, et al, 2021 ; Zhang et al, 2018 ), and the dentate nucleus of the cerebellum (He et al, 2017 ). A previous study using 7.0‐T MRI susceptibility‐weighted imaging of the non‐human primate brainstem indicated that PPN shows higher susceptibility than its adjacent WM structures, such as the SCP and the lemniscal system (Zitella et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] To date, QSM has been performed overwhelmingly in the brain, 2,3,[9][10][11][12][13] and has seen increased adoption in a variety of brain research protocols to study iron, [14][15][16][17][18][19][20][21] myelin, [22][23][24][25] and calcification, 26,27 as well as in clinical protocols such as presurgical mapping of deep brain stimulation targets. [28][29][30][31][32] However, QSM has seen also increasing use throughout the body, which is the focus of this review.…”
mentioning
confidence: 99%
“…Quantitative susceptibility mapping (QSM) 1–4 recovers local tissue susceptibility from the nonlocal fields generated by susceptibility sources in gradient echo (GRE) or balanced steady‐state free precession 5 MRI through 1) saving phase in data acquisition and 2) performing spatial deconvolution according to the dipole field model in magnetism physics 6–8 . To date, QSM has been performed overwhelmingly in the brain, 2,3,9–13 and has seen increased adoption in a variety of brain research protocols to study iron, 14–21 myelin, 22–25 and calcification, 26,27 as well as in clinical protocols such as presurgical mapping of deep brain stimulation targets 28–32 . However, QSM has seen also increasing use throughout the body, which is the focus of this review.…”
mentioning
confidence: 99%